Interval observers design for systems with ostensible Metzler system matrices - Krokavec, Dušan; Filasová, Anna (Frontiers in Aerospace Engineering, 2023)
The paper solves the problem concerning the interval observers design for linear systems with the ostensible Metzler system matrices. Because the system dynamics matrices are partially different from the strictly Metzler structures, the solution is achieved by constructing the composed system matrix representation, which combines pre-compensated interval matrix structures fixed with prescribed region of D-stability and the reconstructed strictly Metzler matrix structure, related to the original interval system matrix parameter definition. A novel design procedure is presented, resulting in strictly positive observer gain matrix and &guaranteeing that the lower estimates of the positive state variables are nonnegative, when considering given system structure and the nonnegative system state initial values The design is computationally simple, since it reduces to the feasibility of the set of linear matrix inequalities.